Keefektifan Metode Role Play terhadap Keterampilan Berbicara Anak di Kelompok B PAUD Tunas Bangsa Kota Bima: The Effectiveness of the Role Play Method on Children's Speaking Skills in Group B PAUD Tunas Bangsa Bima City - Awalunisah, Sita; Sugito, Sugito (Pedagogia : Jurnal Pendidikan, 2018)
This study aims to reveal the effectiveness of role play method on the speaking skill of children in group B PAUD Tunas Bangsa Kota Bima. This research is a quasi experimental research, targeting children of group B in PAUD Tunas Bangsa, Bima Town. Research subjects were 40 children, consisted of 20 children as experimental group and 20 children as control group determined by purposive sampling technique. The experimental group was given treatment of role play method, while the control group was given conventional method. The instrument of data collection is an observation sheet. This research data obtained from the observation at the time before and after learning. The data obtained were then analyzed and tested by t-test statistic to see the difference between the experimental group and the control group. The result of the research there is significant and effectiveness from the role play method on children's speaking skill in group B PAUD Tunas Bangsa, Kota Bima. The significance value of 0.047 with an average difference of 8.3. The result shows that role play method influence to children's speaking skill in group B PAUD Tunas Bangsa Bima Town.